Canine junctional epidermolysis bullosa due to a novel mutation in LAMA3 with severe upper respiratory involvement. Issue 4 (12th July 2021) - Herrmann, Ina; Linder, Keith E.; Meurs, Kathryn M.; Friedenberg, Steven G.; Cullen, Jonah; Olby, Natasha; Bizikova, Petra
Abstract : Background: Junctional epidermolysis bullosa (JEB) is a group of congenital blistering skin diseases characterized by clefting through the lamina lucida of the basement membrane zone. Objectives: To characterize the clinical and morphological features of a congenital mechanobullous disease in a litter of puppies with severe upper respiratory involvement, and to identify an associated genetic variant. Animals: Five of eight puppies in an Australian cattle dog cross‐bred litter showed signs of skin fragility. Three were stillborn and one died at one month of age. The two surviving puppies were presented with blistering skin disease and severe respiratory distress. Additionally, one unaffected sibling was examined and blood was obtained for genetic testing. Methods and materials: Post‐mortem examination, histopathological evaluation and electron microscopy were performed. Whole genome sequencing (WGS) of one affected puppy was compared to a database of 522 dogs of 55 different breeds for variant analysis. Sanger sequencing of one additional affected and one unaffected sibling confirmed the variant. Results: Clinically, severe mucocutaneous ulcers occurred in frictional areas with claw sloughing. Histopathological results revealed subepidermal clefts and electron microscopy confirmed the split in the lamina lucida. Post‐mortem examination documented extensive pharyngeal and laryngeal lesions with granulation tissue and fibrinous exudate obscuring the airway. Moderate tracheal hypoplasia contributed. The WGS revealed a novel missense variant in the laminin α3‐chain XP_537297.2p(Asp2867Val), with an autosomal recessive mode of inheritance. Conclusions and clinical relevance: A novel variant in LAMA3 caused a generalized and severe phenotype of JEB with an unique clinical presentation of upper airway obstruction. Abstract : Background – Junctional epidermolysis bullosa (JEB) is a group of congenital blistering skin diseases characterized by clefting through the lamina lucida of the basement membrane zone. Objectives – To characterize the clinical and morphological features of a congenital mechanobullous disease in a litter of puppies with severe upper respiratory involvement, and to identify an associated genetic variant. Conclusions and clinical relevance – A novel variant in LAMA3 caused a generalized and severe phenotype of JEB with an unique clinical presentation of upper airway obstruction. Résumé: Contexte: L'épidermolyse bulleuse jonctionnelle (JEB) est un groupe de dermatoses cutanées congénitales vésiculeuses caractérisées par un clivage au niveau de la lamina lucida de la membrane basale. Objectifs: Caractériser les critères cliniques et morphologiques de maladies bulleuses congénitales dans une portée de chiots avec troubles respiratoires sévères et identifier un variant génétique associé. Sujets: Cinq des huit chiots d'une portée de chiens croisés bouvier australien ont montré des signes de fragilité cutanée. Trois étaient mort‐nés et un est mort à l'âge d'un mois. Les deux chiots survivants ont été présentés avec une dermatose vésiculeuse et des troubles respiratoires sévères. En outre, un chiot sain a été examiné et du sang a été prélevé pour tests génétiques. Matériels et méthodes: Un examen post‐mortem, une évaluation histopathologique et electro‐microscopique ont été réalisés. Le séquençage complet du génome (WGS) d'un chiot atteint a été comparé à une base de données de 522 chiens de 55 races différentes pour une analyse de variant. Le séquençage de Sanger d'un autre chiot atteint et un chiot sain a confirmé le variant. Résultats: Cliniquement, les ulcères cutanéo‐muqueux sévères étaient observés aux zones de friction avec pertes des griffes. Les résultats histopathologiques révélèrent des séparations sous épidermiques et l'électro‐microscopie a confirmé le clivage au sein de la lamina lucida. L'examen post mortem a documenté des lésions laryngées et pharyngées extensives avec tissue de granulation et exsudat fibrineux dissimulant les voies aériennes. Une hypoplasie trachéale modérée y contribuait. Le WGS a révélé un nouveau variant contre‐sens dans la chaine α3 de laminine XP_537297.2p(Asp2867Val), avec un mode autosomal récessif de transmission. Conclusions et importance clinique: Un nouveau variant cause un phénotype de JEB sévère et généralisé avec une présentation clinique unique d'obstruction des voies respiratoires supérieures. Resumen: Introducción: la epidermólisis bullosa de la unión (JEB) es un grupo de enfermedades cutáneas congénitas con formación de ampollas caracterizadas por una hendidura a lo largo de la lámina lúcida de la zona de la membrana basal. Objetivos: establecer las características clínicas y morfológicas de una enfermedad mecanobullosa congénita en una camada de cachorros con afectación respiratoria superior grave e identificar una variante genética asociada. Animales: cinco de los ocho cachorros en una camada mestiza de perros de ganado australiano mostraron signos de fragilidad de la piel. Tres nacieron muertos y uno murió al mes de edad. Los dos cachorros supervivientes presentaron una enfermedad cutánea con ampollas y dificultad respiratoria grave. Además, se examinó a un hermano no afectado y se extrajo sangre para realizar pruebas genéticas. Métodos y materiales: Se realizó examen post‐mortem, evaluación histopatológica y microscopía electrónica. La secuenciación del genoma completo (WGS) de un cachorro afectado se comparó con una base de datos de 522 perros de 55 razas diferentes para el análisis de variantes. La secuenciación de Sanger de un hermano afectado adicional y un hermano no afectado confirmó la variante. Resultados: Clínicamente, se produjeron úlceras mucocutáneas graves en áreas de fricción con desprendimiento de garras. Los resultados histopatológicos revelaron hendiduras subepidérmicas y la microscopía electrónica confirmó la escisión en la lámina lúcida. El examen post‐mortem documentó extensas lesiones faríngeas y laríngeas con tejido de granulación y exudado fibrinoso que oscurecía las vías respiratorias. A las lesions también se añadía una hipoplasia traqueal moderada. El WGS reveló una nueva variante sin sentido en la cadena α3 de laminina XP_537297.2p (Asp2867Val), con un modo de herencia autosómico recesivo. Conclusión y relevancia clínica: una nueva variante genética causó un fenotipo generalizado y severo de JEB con una presentación clínica única de obstrucción de las vías respiratorias superiores. Zusammenfassung: Hintergrund: Die Junctional Epidermolysis Bullosa (JEB) umfasst eine Gruppe kongenitaler blasenbildender Hauterkrankungen, die durch eine Spaltbildung durch die Lamina lucida der Basalmembranzone charakterisiert sind. Ziel: Die Charakterisierung klinischer und morphologischer Merkmale einer kongenitalen mechanobullösen Erkrankung bei einem Wurf von Welpen mit hochgradiger respiratorischer Beteiligung sowie eine Identifizierung der damit zusammenhängenden genetischen Variante. Tiere: Fünf von acht Welpen eines Australian cattle Dog Mischlingswurfes zeigten Zeichen von Hautfragilität. Drei waren totgeboren und ein Welpe starb mit einem Monat. Die zwei überlebenden Welpen wurden mit einer blasenbildenden Hauterkrankung und hochgradiger respiratorischer Not vorgestellt. Zusätzlich wurde ein nicht betroffenes Geschwister untersucht und Blut zur genetischen Analyse genommen. Methoden und Materialien: Eine Post Mortem Untersuchung, eine histopathologische Evaluierung und Elektronenmikroskopie wurden durchgeführt. Eine Ganz‐Genom Sequenzierung (WGS) eines erkrankten Welpen wurde mit der Datenbank von 522 Hunden 55 verschiedener Rassen zur Varianzanalyse verglichen. Mittels Sanger Sequenzierung eines der weiteren betroffenen und eines nicht erkrankten Geschwisters wurde die Variante bestätigt. Ergebnis: Klinisch traten hochgradige mukokutane Ulzera an Reibungsstellen auf, wobei sich die Krallen ablösten. Die histopathologische Untersuchung ergab subepidermale Spalten und mittels Elektronenmikroskopie wurde der Spalt in der Lamina lucida bestätigt. Die Post mortem Untersuchung dokumentierte ausgedehnte Läsionen in Pharynx und Larynx, wobei Granulationsgewebe und fibrinöses Exsudat die Luftwege behinderten. Eine moderate tracheale Hypoplasie trug zu dem Problem bei. Die WGS zeigte eine neue Missense Mutation in der Laminin α3‐Kette XP_537297.2p(Asp2867Val), bei autosomal rezessiver Vererbung. Schlussfolgerungen und klinische Bedeutung: Eine neue Variante bedingte eine generalisierte Form einer JEB mit einem stark betroffenen Phänotyp und einer einzigartigen klinischen Präsentation der Obstruktion der oberen Atemwege. 要約: 背景: Junctional epidermolysis bullosa（JEB）は，基底膜領域のlamina lucidaを介した間隙を特徴とする先天性水疱性皮膚疾患の一群である。 目的: 本研究の目的は、重度の上気道病変を有する子犬集団における先天性機械的水疱性疾患の臨床的および形態学的特徴を明らかにし，関連する遺伝子変異を同定することであった。 供試動物: オーストラリアン・キャトル・ドッグとの交配で生まれた子犬8頭のうち、5頭に皮膚脆弱性の兆候が見られた。3頭は死産し、1頭は生後1ヶ月で死亡した。生き残った2頭の子犬は、水ぶくれのある皮膚病と重度の呼吸困難を呈していた。さらに、罹患していない1頭の同腹仔を診察し、遺伝子検査のために血液を採取した。 材料と方法: 死後検査、病理組織学的評価および電子顕微鏡検査を行った。罹患子犬1頭の全ゲノム塩基配列（WGS）を、55種の犬522頭のデータベースと比較し、バリアント解析を行った。さらに罹患した1頭の同腹仔と罹患していない1頭の同腹仔のサンガーシークエンス法により、変異が確認された。 結果: 臨床的には、重度の粘膜皮膚潰瘍が摩擦部位に発生し、爪が剥がれた。病理組織学的には表皮下の間隙を認め、電子顕微鏡ではlamina lucidaの間隙が確認された。死後検査では、肉芽組織および線維性滲出液が気道を塞いでいる広範囲の咽頭および喉頭の病変が記録された。中等度の気管低形成が認められた。WGSの結果、ラミニンα3鎖のXP_537297.2p(Asp2867Val)という新規ミスセンス変異が見つかり、常染色体劣性遺伝であることが判明した。 結論と臨床的妥当性: 新規変異は、上気道閉塞というユニークな臨床症状を伴うJEBの全般的で重篤な表現型の原因となった。 摘要: 背景: 交界性大疱性表皮松解症(Junctional epidermolysis bullosa，JEB)是一组先天性水疱性皮肤病，以基底膜区透明层裂隙为特征。 目的: 描述一窝严重上呼吸道发病幼犬先天性机械大疱病的临床和形态学特征，并确定相关的遗传变异。 动物: 澳大利亚杂交牛犬8只同窝幼犬中的5只显示出皮肤脆弱症状。3只为死胎，1例在1月龄时死亡。2只存活幼犬表现为水疱性皮肤病和严重呼吸窘迫。此外，检查了1只未发病的同窝犬，并采集血液用于基因检测。 方法和材料: 进行尸检、组织病理学评价和电子显微镜检查。将1只发病幼犬的全基因组测序(WGS)与55个不同品种的522只犬的数据库进行比较，进行变异分析。对另外一个发病和一个未发病的同窝犬进行Sanger测序，证实了该变异。 结果: 临床上，重度皮肤粘膜溃疡发生在摩擦区域，伴爪脱落。组织病理学结果显示表皮下裂隙，电子显微镜检查证实透明层开裂。尸检记录了广泛的咽部和喉部病变，伴有肉芽组织和纤维蛋白性渗出物阻塞气道。导致中度气管发育不全。WGS揭示了层粘连蛋白α3‐链XP_537297.2p(Asp2867Val)的一个新的错义变体，具有常染色体隐性遗传模式。 结论和临床相关性: 种新变体引起JEB的广泛和严重表型，具有上呼吸道阻塞的独特临床表现。 Resumo: Contexto: A epidermólise bolhosa juncional (EBJ) é um grupo de doenças cutâneas congênitas apresentando lesões bolhosas caracterizadas por fissuras ao longo da lâmina lúcida da zona da membrana basal. Objetivos: Detalhar as características clínicas e morfológicas de uma doença mecanobolhosa congênita em uma ninhada de filhotes de cães com comprometimento respiratório superior grave e identificar uma variante genética associada. Animais: Cinco dos oito filhotes em uma ninhada com cães boideieros australianos mestiços apresentaram sinais de fragilidade da pele. Três nasceram mortos e um morreu com um mês de idade. Os dois cachorros sobreviventes apresentaram dermatopatia bolhosa e dificuldade respiratória grave. Além disso, um irmão não afetado foi examinado e o sangue foi obtido para teste genético. Métodos e materiais: Foram realizados exame post‐mortem, avaliação histopatológica e microscopia eletrônica. O sequenciamento do genoma completo (WGS) de um filhote afetado foi comparado a um banco de dados de 522 cães de 55 raças diferentes para análise de variantes. O sequenciamento de Sanger de um irmão afetado adicional e um irmão não afetado confirmou a variante. Resultados: Clinicamente, úlceras mucocutâneas graves ocorreram em áreas de fricção com arranhadura pelas unhas. Os resultados histopatológicos revelaram fissuras subepidérmicas e a microscopia eletrônica confirmou a fissura na lâmina lúcida. O exame post‐mortem documentou lesões laríngeas e faríngeas extensas com tecido de granulação e exsudato fibrinoso obscurecendo as vias aéreas. Hipoplasia traqueal moderada contribuiu. O WGS revelou uma nova variante missense na cadeia α3 da laminina XP_537297.2p (Asp2867Val), com um modo de herança autossômico recessivo. Conclusão e relevância clínica: Uma nova variante causou um fenótipo generalizado e grave de EBJ com uma apresentação clínica única de obstrução das vias aéreas superiores.